Uma Ferramenta Web Baseada em LLMs para Respostas a Perguntas Simples sobre Bases de Conhecimento Heterogêneas - Campos, João Pedro Porto; Machado, Marcelo; Lima, Guilherme; Silva, Viviane Torres da (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
We present KIF-QA, a Web tool for answering simple questions over heterogeneous knowledge graphs. The Web tool is built on top of a homonymous framework, KIF-QA, that uses in-context learning over off-the-shelf pre-trained large language models for semantic parsing. Because it relies on in-context (few-shot) learning to generate logical forms and disambiguate entities, and because it uses KIF (a knowledge integration framework based on Wikidata) to mediate all access to the target knowledge graphs, KIF-QA’s approach is general. It requires neither training nor fine-tuning and can be easily adapted to work with different graphs. The KIF-QA Web tool allows the user to change the target graphs (Wikidata, DBpedia, or PubChem) and the language model used. The user can also view and modify the details of each step taken by KIF-QA to generate the answers to the question. Both the Web tool and the KIF-QA framework are released as open-source.